ANALISIS TANAH LONGSOR DI TENJOLAYA MENGGUNAKAN DATA PENGINDERAAN JAUH - Haryani, Nanik Suryo (MAJALAH ILMIAH WIDYA, 2012)
The landslide in Tenjolaya Village, Pasir Jambu Sub district, Bandung District on February 23, 2010 was triggered by a heavyrainfall on previous day. The aim of the research is to analyze the landslide occurrence based on remote sensing data in TenjolayaVillage. The data analyze uses satellite images MTSAT-1R and QMORPH, and physical condition around Bandung, which can beseen from various remote sensing images, among others ALOS and IKONOS images. The result of rainfall analysis from MTSATsatellite shows a probability of heavy rainfall on previous day, and QMORPH data shows the heavy to very heavy rainfall. MeanwhileALOS and IKONOS images shows that the morphology around the landslide area is a tea plantation field located in the high mountainouscoverage with landslide sensitive properties.